Added Value Field Study on The Saudi Society - Al Zahrani, Ali Hassan; Aljaid, Waed Awaid; Al Harthy, Sadeem Osman; Al Thubaiti, Hadeel Abdullah; Al Ghamdi, Samar Said; Al Harthy, Muznah Saad (Journal of Economic, Administrative and Legal Sciences, 2018)
The research treated the Value Added Tax which King Saudi Arabia has committed to apply the world’s lowest VAT rates by 5%, starting from 1 January 2018 after the entry into force of the value added tax, held by the unified agreement between the GCC countries. The aim of the research is the issue of the value added tax has raised a wide debate in the Gulf society in general and the Saudi society in particular. The search interest in the importance of the value added tax - added benefits, the Saudi society’s awareness of the value added tax, recognition of the satisfaction of the people, regarding the value added tax ratio, the difference between the sales tax and the value added tax, the penalty of tax manipulation and methods of reporting in case of applying that in application, and privileges obtained by companies when applying value added tax. There are no previous studies of the value added tax, held by in KSA because it is a new addition in the kingdom that no one has ever researched. The statistical approach was used in this study. A questionnaire consisting of several expressions was distributed and distributed in social media in order to collect as many views as possible. This study proved that the Saudi society has knowledge and knowledge of the definition of value added and is satisfied with this ratio, which is 5%, but most are not aware of the following things: Goods exempted from VAT, Reasons for VAT, the penalty of manipulation of value added tax, Method of reporting violations by applying value added, and privileges obtained by companies when applying value added. The research also has several recommendations that can be pf benefit to introduce Saudi society to value added, including: awareness-raising programs with added value, including the need to rationalize consumption of goods and reduce spending on luxury goods. Warning citizens of ways to exploit the shops for tax, work control of facilities to reduce the exploitation of the tax.